Impact of nutritional education strategies on anthropometric variables and nutrition knowledge - Ana Carolina Marques Gomes; Carolina Paudarco Dias; Roseli Oliveira Guerra; Vera Lúcia Morais Antonio de Salvo (Universidade de Fortaleza, 2014)
Objective: To assess the impact of a nutrition education program on the nutritional status and food knowledge of patients with overweight. Methods: A longitudinal quantitative study, performed between September and October 2012, with sample consisting of 15 patients with excessive weight (overweight: Body Mass Index or BMI between 25kg/m2 and 29,9kg/m2; and obesity: above 30kg/m2), enrolled in a group of food education in a Primary Healthcare Unit. Nutritional intervention occurred in six weekly meetings (M1: general screening; and M7 to M2: 6 nutritional interventions), being applied a questionnaire assessing the participants' knowledge on the subjects to be discussed before and after the intervention. Prior to the first meeting and in the last intervention, measures of weight, height and waist circumference were obtained. Nonparametric Wilcoxon tests were performed, with a significance level of 5%, to analyze the average number of correct answers and the nutritional outcome. Results: Following the nutritional education strategy, there was an average reduction of 1.51kg in relation to the initial weight; the average BMI increased from 37.41kg/m² to 36.85kg/m²; waist circumference showed mean reduction of 5.6cm; and the number of correct answers in the questionnaires increased. Conclusion: The nutritional education strategy seems to have influenced the good evolution of the participants' nutritional status, leading to a decrease in the anthropometric measures and increasing knowledge about healthy eating. doi: http://dx.doi.org/10.5020/18061230.2013.p462